Composite H3PW12O40–TiO2 catalysts for toluene selective photo-oxidation - Bertolini, Guillermo Ramon (2018)
A series of composite systems based on titania and growing quantities of tungstophosphoric acid are prepared and characterized using infrared, nuclear resonance, UV–visible, photoluminescence, and photoelectron spectroscopies, transmission electron microscopy as well as x-ray diffraction and porosimetry techniques. These techniques showed evolution of the tungstophosphoric acid species supported into titania while this majority component of the system suffers minor changes. The activity and stability of the composite samples for gas phase toluene photo-oxidation under UV and sunlight-type irradiation conditions was measured by means of the reaction rate and the photonic efficiency parameter. The modeling of the radiation field was accomplished by numerically solving the radiative transfer equation. The photo-activity of the composite materials showed a significant selectivity towards the transformation of the hydrocarbon into a partially oxidized product, benzaldehyde. Both the activity and selectivity of the titania are significantly affected by the presence of tungstophosphoric acid species. The physico-chemical characterization was able to point out to the leading role of specific polytungstate species in driving the enhancement of the activity and selectivity of the reaction, rendering stable, highly active and selective photo-catalysis.